USE OF INFORMATION TECHNOLOGY IN THE PROCESS OF FORMING ECOLOGICAL COMPETENCE OF PUPILS ON THE PHYSICS LESSONS - Sharko В.Д.; Kurilenko Н.В. (Journal of Information Technologies in Education (ITE), 2011)
In article considered approach to definition of concepts “competence”,«ecological competence», and on basis their characterized of the role, importance and ways forming of a ecological competence pupils in process of training physics in general school.